RANCANG BANGUN APLIKASI INFORMASI RUTE BUS MAYASARI BAKTI DENGAN ALGORITMA KNUTH- MORRIS-PRATT BERBASIS ANDROID - Fransiscus Xaverius Syahasta A.T.; Seng Hansun (Universitas Kristen Duta Wacana, 2016)
This research is about design and development of information application of Mayasari Bakti buses’ route for smartphones based on Android operating system. To search for the expected bus, this application implements Knuth-Morris-Pratt Algorithm. The application was tested on 41 respondents and the result is very useful to search for one until two buses which can take the passengers from an origin to destination location which have been selected before, and show it up on a map.